Membangun Insan Kamil dari Perspektif Media; Media Literasi sebagai Kontrol Sosial - Khomsiyatul Mukarromah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2016)
Insan kamil (the perfect human) is the most ideal concept in achieving the best quality of human being in all its dimensions. The extent of media influence on the knowledge, attitude, mental, and spiritual quality of human being is not something that needs to be debated again. Television with its capacity has the same great potential as a driving force or a barrier at the same time for the development of human quality. A growing phenomenon about the content of television in Indonesia is increasingly revealing the colors of mourning in its massive dissemination. The composition of the broadcast is full with entertainment which is ranging from the telenovela, infotainment, reality show, charity show, comedy, crime to other news are very far from the role of educating. Thus, where are broadcasting program rules that must contain 70% of the educative elements? Even an impressed classy broadcasting program such as talk show which is hosted by an “educated person” have not been off completely from the framing of the media. This paper seeks to offer a media literacy concept in response to these problems. Media literacy is an ability to access, understand, analyze, evaluate, and producing media information in a variety of contexts. This is intended so that the community can afford to be critical and creative, not merely subject to exploitation by the media but make them explore and have media skilled.